Comparisons of mortality and rehospitalization between hip-fractured elderly with outpatient rehabilitation and those without: A STROBE-compliant article. Issue 19 (May 2018) - Pan, Po-Jung; Lin, Pin-Hsun; Tang, Gau-Jun; Lan, Tzuo-Yun
Abstract : Abstract: Geriatric patients with hip fractures have high mortality. This study aimed to compare the mortality and rehospitalization of recipient and nonrecipient of outpatient rehabilitation in hip-fractured elderly. This retrospective cohort study used nationwide claims data in Taiwan and included 3585 senior citizen patients admitted for hip fractures between January 1, 2005, and December 31, 2012. Patients were divided into the recipient (717) and nonrecipient (2868) of outpatient rehabilitation during the first 3 months after hospital discharge. Each patient was followed up for 1 year. Mortality rates of hip-fractured elderly after discharge during the first 3-month period in different groups were analyzed with Chi-square test. Cox proportional hazards regression model was employed for both death and rehospitalization risk analyses. The mortality rate of the rehabilitation group was lower than that of the nonrehabilitation group (12.69% vs 16.70%, P < .05). A more beneficial effect was observed for patients receiving continuous rehabilitation. The rehabilitation group had a lower adjusted risk of death [hazard ratio (HR) = 0.74; 95% confidence interval (95% CI): 0.59–0.94] than that of the nonrehabilitation group. However, the rehabilitation group was at a higher risk of rehospitalization (HR = 1.37; 95% CI: 1.22–1.55). Hip-fractured elderly receiving outpatient rehabilitation have a lower risk of death but a higher risk of rehospitalization than those not receiving rehabilitation within 1 year after fracture.